THE EFFECTS OF USING PICTURE SERIES ON THE WRITING PROCEDURE TEXTS OF THE SECOND YEAR STUDENTS OF MTS DARUL FUNUN EL-ABBASIYAH KABUPATEN 50 KOTA - Vebria Fauzana; Fadly Azhar; M Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this reserach was to improve the students' skills in writing procedure texts by using picture series for the eighth grade students of MTs Darul Funun El-Abbasiyah Kabupaten 50 Kota in the academic year of 2016/2017. The research was pre-experimental research. The samples of the research consisted of the students of Grade VIII 3. To get the data, the researcher conducted a written test in pre-test and post-test. The pre-test and post-test were conducted to gain the quantitative data. Score of pre-test and the post-test were used to analyze the quantitative data that were in the form of students' writing scores. The findings showed that picture series effectively improved the students’ skills in writing procedure texts. The improvements covered: 1) the students considered writing as an easy and interesting lesson, indicated by their enthusiasm to write, 2) students generated and organized their ideas more easily in a good order, 3) and picture series improved the students' skills in writing procedure texts in terms of grammar, vocabulary, and sentence structure. The researcher found that the students’ writing skills were improved. It can be seen from their main scores of pre-test and post-test. There was an improvement between the pre-test mean score (45.29) and the post-test mean score (70.20). The gained scores of the means was (24.91), so it can be concluded that the use of picture series could improve the students’ writing skills of procedure texts.Keywords: Effect, Picture Series, Writing, Procedure Text